Exploring the Underlying Impediments to Talent Retention in the Public Service: Experience from Nigeria - Anas, Aminu A.; Alahakone, Ratnesvary; Perdikis, Nicholas (Journal of Management Policy and Practice, 2020)
This paper explored the underlying impediments to talent retention in the Federal Civil service in Nigeria. The federal service faces challenges of retaining talents, thereby resulting in the inability to preserve and transfer knowledge, increased turnover cost and lack of talent succession in the service. Varying commissions of inquiry and fact-finding teams set up to attract and retain talents in the Federal Civil service as a measure of improving performance towards effective and efficient service delivery in nation-building. Existing literature provided the basis for the conceptual and theoretical clarifications of the problem statement. The study adopted a mixed-method approach. A sample of respondents of 149 purposively selected for the research. Factor analysis, ANOVA and content and thematic analysis deployed for both quantitative and qualitative analysis of data with the aid of SPSSv25(for quantitative data) and Nvivo 10(for the qualitative results). The study recommends that there should be an attempt to focus on talent retention in public service, as it is critical to the implementation of government policies. Further, the need for talent management policies and guidelines that will provide a framework for managing talent in the Federal Service is more pertinent now than ever for the sustainability of democratic rule. The study also makes a theoretical contribution through the validation of the cost-benefit theory.